2021
DOI: 10.3390/plants10081665
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Functional Analysis of a PISTILLATA-like MADS-Box Gene from Argan Tree (Argania spinosa)

Abstract: Argan trees (Argania spinosa) belong to a species native to southwestern Morocco, playing an important role in the environment and local economy. Argan oil extracted from kernels has a unique composition and properties. Argan trees were introduced in Tunisia, where hundreds of trees can be found nowadays. In this study, we examined reproductive development in Argan trees from four sites in Tunisia and carried out the functional characterization of a floral homeotic gene in this non-model species. Despite the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…These ratios give clues about cellular localization by indicating in which cell sub-region a protein is more likely to be found. Similar to our findings here, MADS-box proteins were also reported to be located in nucleus in Argania spinosa by Louati et al ( 2021 ) and in Setaria italica L. by Zhao et al ( 2021 ) in recent years.…”
Section: Resultssupporting
confidence: 92%
“…These ratios give clues about cellular localization by indicating in which cell sub-region a protein is more likely to be found. Similar to our findings here, MADS-box proteins were also reported to be located in nucleus in Argania spinosa by Louati et al ( 2021 ) and in Setaria italica L. by Zhao et al ( 2021 ) in recent years.…”
Section: Resultssupporting
confidence: 92%
“…Despite the difficulties in argan tree propagation, several attempts have been made in the past or are under experimentation to promote argan domestication outside its natural range. The oldest attempts have been probably made in 1800 in the colonies of the East Indies (Hooker 1854), while in 1960s several introductory trials have been made in Tunisia (Louati et al 2021), even if already in 1924 Emberger (1924) reported the presence of argan trees around Kairouan (Tunisia) although this information has not been validated by botanists at the time. According to Louati et al (2019) the introduction of argan in Tunisia could result in a positive impact on the economic situation of rural areas, especially as argan tree is suitable to be cultivated in less fertile and almost abandoned areas of Tunisia.…”
Section: Specialized Cultivations Of Argan Trees and Possibilities Fo...mentioning
confidence: 99%
“…In core eudicots, most GLO-/PI-like genes, such as EjPI from Eriobotrya japonica [26], GGLO1 from Gerbera hybrida [27], and AsPI from Argania spinosa [28], were expressed in the petal and stamen and were mainly required in controlling perfect petal and stamen identities during flower development. The data indicate that the functions of GLO-/PI-like genes are highly correlaTaKaRa, Shigated with their expression zones in core eudicots.…”
Section: Discussionmentioning
confidence: 99%